Competitive surfing: A physiological profile of athletes and determinants of performance - Farley, O. (2011)
Despite a huge growth in competitive surfing there is still a paucity of research available to underpin assessment and conditioning practice. Limited research investigating surfers` aerobic and anaerobic fitness provides an initial insight into the physiological demands of surfing; however it is limited in terms of competitive surfing and is characterized by methodological discrepancies. Likewise performance analysis has not been utilized extensively in surfing. Information available to-date suggests that competitive surfing is characterized by repeat high intensity intermittent bouts of paddling interspersed with moderate and high heart rates. Additionally, research evidence indicates that surfers possess moderately high aerobic fitness levels, comparable to other athletic groups such as competitive swimmers and surf life savers. To understand more about the sport of surfing, fundamental research into competitive surfing is needed. Therefore, the objectives of this study were to use methods of performance analysis to measure the physical outputs, workloads and activity patterns of elite surfers during competitions, and to specifically measure their anaerobic power output and peak oxygen uptake (VO2peak) on a modified kayak ergometer, and the relationship between these outputs and surfing performance.